Honey, why don't you see a doctor? Spousal impact on health behavior - Stefanie Neimann; Hendrik Schmitz (Verein für Socialpolitik, 2010)
Married individuals are usually found to be in better health than singles but it is not fully known why. Using data from the German Socio-Economic Panel we test one possible explanation, namely that two spouses encourage each other to a health-promoting behavior and monitor it. Therefore, we analyze the direct spousal impact on seeking medical advice, physical activity, and eating habits controlling for selection, positive assortative mating, and shared unobserved influences of the environment. While we find no causal effect regarding a health-conscious diet, the impact of the partner's doing sports is substantial. Moreover, females affect their male spouses in seeking medical advice but not the other way around. The latter result may explain why men usually benefit more from marriages than women.
Keywords: C33; I12; J12; 330; Couples; health behavior; simultaneous equations models